Pen and paper or computerized notetaking? L2 English students’ views and habits - Joseph Siegel (Computers and Education Open, 2023)
Many students have the option of taking notes using the traditional pen and paper method or using computers to take notes digitally. Decisions about which notetaking method to use can be particularly important for students operating in a second language (L2), as they often face challenges in listening comprehension and note production in comparison to working in their first language (L1). While empirical research has begun to investigate which notetaking method might be more beneficial in terms of note content and lecture comprehension, less is known about how preference for pen and paper or computerized notetaking may affect views of notetaking and notetaking habits. Therefore, this paper builds on previous survey studies on student notetaking by comparing responses from those who prefer taking notes with pen and paper with those who prefer computerized notetaking. In addition, while much research has focused on students listening to content and taking notes in their L1, participants in this study were doing so in English as an L2. Data from 385 participants across four countries was collected via an online survey, and 2 × 2 chi squared tests of independence were used to determine any differences between those who prefer pen and paper and those who prefer computerized notetaking in relation to statements about and habits related to notetaking. Results showed more differences in opinions, in particular related to feelings about comprehension and concentration levels, and more consistency in notetaking habits. Implications are discussed in relation to levels of processing and encoding theories as well as to previous research.